With or without a Tourniquet? A Comparative Study on Total Knee Replacement Surgery in Patients without Comorbidities - Albayrak, Mehmet; Ugur, Fatih (MDPI AG, 2023)
Background and Objectives: This study aimed to determine the effects of tourniquet use and the complications of total knee arthroplasty (TKA) in patients without comorbidities to investigate whether tourniquet application can be employed without adverse effects and to assess its impact on the occurrence of any complications. Materials and Methods: A total of 106 patients who underwent unilateral TKA were divided randomly into two groups according to whether a tourniquet was used during the surgery or not. Patients with comorbidities (except arterial hypertension) were excluded from the study. Knee Injury and Osteoarthritis Outcome Score, joint range of motion, visual analog scale (VAS) score, total blood loss during and after surgery, postoperative analgesic consumption, and side effects were the main factors evaluated in the study. Results: In the tourniquet group, where the VAS scores were higher, the use of analgesics was also significantly higher. While there was no statistically significant difference in total blood loss between the tourniquet and non-tourniquet groups, the postoperative and occult blood losses were higher in the tourniquet group. The differences between the two groups in all other parameters were very small and not statistically significant. Conclusions: The findings of the current study suggest that when the comorbidities of patients are thoroughly documented and clarified prior to surgery, tourniquets should be applied selectively to individuals without any pre-existing health conditions.
Keywords: total knee arthroplasty; Medicine (General); Pain, Postoperative; Blood Loss, Surgical; Osteoarthritis, Knee; Tourniquets; comorbidities; Article; R5-920; comorbidities; total knee arthroplasty; tourniquet; pain; Humans; pain; Range of Motion, Articular; Arthroplasty, Replacement, Knee; tourniquet; 3. Good health